PENGARUH MANAJEMEN SARANA PRASARANA DAN IKLIM SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI DI KECAMATAN JATIBARANG KABUPATEN INDRAMAYU - Dedi Sutansyah (Edum Journal, 2019)
The focus of this research is to know and analyze the influence of infrastructure management on teacher performance, school climate influence on teacher performance and the influence of school facilities and school infrastructure management simultaneously on the performance of public junior high school teachers in Jatibarang Subdistrict, Indramayu Regency. Research design using casuality study. Data collection techniques by distributing questionnaires to 60 public junior high school teachers at the Subdistrict Jatibarang Indramayu Regency. The results showed that: (1) The management of facilities and infrastructure had a strong influence on teacher performance, from the correlation coefficient analysis obtained r value = 0.436, meaning that there is a correlation that is moderate. (2) School climate has a moderate effect on teacher performance, from correlation coefficient analysis obtained r value = 0,493, meaning that there is correlation which is moderate. (3) The management of infrastructure and work facilities simultaneously has a strong effect on the performance of teachers at public junior high school in Jatibarang Subdistrict, Indramayu Regency. The authors suggest, that: (1) In order to maintain the performance of teachers, even further to improve teacher performance to a better direction again. Consideration should be given to maintaining the comfort of school climate through improving interpersonal relationships, system changes and the physical environment surrounding schools. (2) In order to improve the performance of teachers can be done through the provision of learning infrastructure facilities through the management of learning tools. Maintain the availability of teaching aids and teaching media as well as regular monitoring so that the existence and adequacy of learning equipment is more secure.